Innovations in rural and agricultural finance: Financial literacy - Cohen, Monique (International Food Policy Research Institute, 2010)
The global financial crisis has intensified the problems of over-indebtedness, especially for the poor. In this context, the microfinance industry is giving more attention to building their customers' financial capabilities, designing products that respond to their needs and preferences, and ensuring their protection as consumers.